2019
DOI: 10.17718/tojde.640510
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the Concept and Dimensions of Professional Functions in Online Learning System of Medical Sciences: A Qualitative Content Analysis

Abstract: The increasing growth of technology affects all aspects of life, including the system of education, and requires the implementation of a new education system. Since Electronic-learning (E-L) is a new and mutated form of education in Iran, its professional functions approach is different from that of traditional education. The present article aims to explain the concept and dimensions of professional functions in this field. Through a qualitative study, method and data source triangulation were used. To do so, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Heuristic information means that after learning a learning object, the learner will choose the learning object that suits him according to his 5 Wireless Communications and Mobile Computing intuition. Intuition mainly includes one's own knowledge level, learning style, and media preference [16,17]. Learners will compare their own knowledge level with the difficulty of the learning object, their own learning style, and the applicable style of the learning object.…”
Section: Inspirational Informationmentioning
confidence: 99%
“…Heuristic information means that after learning a learning object, the learner will choose the learning object that suits him according to his 5 Wireless Communications and Mobile Computing intuition. Intuition mainly includes one's own knowledge level, learning style, and media preference [16,17]. Learners will compare their own knowledge level with the difficulty of the learning object, their own learning style, and the applicable style of the learning object.…”
Section: Inspirational Informationmentioning
confidence: 99%
“…The three most common principal subjects in the 39 reviewed papers were: exercises to define and describe e-learning as a concept (Adam et al, 2013;Al Zahrani & Kumar, 2015;Cardona-Román & Sánchez-Torres, 2011;Crescente & Lee, 2011;Denham et al, 2012;Grant, 2019;Hartley & Andújar, 2022;Ismuratova et al, 2017;Kergel & Heidkamp-Kergel, 2021;Khoury et al, 2011;Kumar Basak et al, 2018;Li, 2018;Mirmoghtadaie et al, 2019;Moore et al, 2011;Nagy, 2016;Rodrigues et al, 2019;Vagarinho, 2020;Vagarinho, 2018)); descriptions of the concept or implementation of specific e-learning programmes (Al-rahmi et al, 2015;Arzayeva et al, 2015;Kobewka et al, 2014;Launay-Vacher & Rieutord, 2014;Lewis et al, 2014;Martínez-Gómez et al, 2022); and, the use of artificial intelligence, machine learning, or semantic web technology to suggest and provide learning objects based on a learner's requirements (Ahmed et al, 2018;Kavitha & Lohani, 2019;Moubayed et al, 2018;Sengupta et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In a study carried out by Mirmoghtadaie et al (2019), it was found that students who have medical education through e-learning methods had no idea whether this education method increased their academic success or not. Considering the answers of the students to the MATDLS that developed in this study, it was found that the students believe that e-learning increases their academic success.…”
Section: Results Discussion and Recommendationsmentioning
confidence: 99%